Pengaruh Penggunaan Teknologi Kecerdasan Buatan bagi Pembelajaran Mahasiswa - Aisyah, Siti Nur (Jurnal Pelita Teknologi, 2022)
The use of artificial intelligence (AI) technology at a time when the educational paradigm is changing serves as the driving force behind this study. This study aims to assess how AI adoption affects higher education students' learning. The research examines literature on the application of AI in higher education in order to accomplish this aim. The findings demonstrate that the application of AI technology has the potential to improve the efficacy of learning through the personalization of the learning process, the development of students' future-ready abilities, and the creation of a more flexible learning environment. Thus, AI in higher education creates a wealth of chances for creative thinking in the classroom. However, in order to combine technology with fundamental educational concepts, ethical concerns and accountability are necessary.